2022
DOI: 10.1108/jabs-06-2021-0240
|View full text |Cite
|
Sign up to set email alerts
|

Testing the stress‐strain‐outcome model in Philippines‐based call centers

Abstract: Purpose The purpose of this paper is to examine the relationships between perceived customer unfriendliness, emotional exhaustion, emotional dissonance and turnover intent using the stress–strain–outcome model in the call center industry in the Philippines. In addition, this paper also investigates the mediating effects of leader–member exchange (LMX) and emotional exhaustion. Design/methodology/approach This paper proposed a theoretical model hypothesizing the linkages between the abovementioned variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Employees are unwilling to engage in proactive PEBs as a result of JIS and emotional exhaustion. The finding with respect to emotional exhaustion as a mediator between JIS and proactive PEB is not only consistent with the stress-strain-outcome model but also obtains support from other studies [27,76,77]. Specifically, employees with the experience of threat and high levels of uncertainty about their jobs are emotionally exhausted at elevated levels and therefore display diminished proactive PEBs.…”
Section: Key Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…Employees are unwilling to engage in proactive PEBs as a result of JIS and emotional exhaustion. The finding with respect to emotional exhaustion as a mediator between JIS and proactive PEB is not only consistent with the stress-strain-outcome model but also obtains support from other studies [27,76,77]. Specifically, employees with the experience of threat and high levels of uncertainty about their jobs are emotionally exhausted at elevated levels and therefore display diminished proactive PEBs.…”
Section: Key Findingssupporting
confidence: 87%
“…For example, Hsieh et al [76] reported that ostracizing behaviors heightened Taiwanese restaurant employees' job tension that in turn resulted in higher proclivity to display nonattendance. Another study indicated that customer unfriendliness aggravated Filipino call center employees' emotional exhaustion, leading to turnover intentions at high levels [77]. In view of the stress-strain-outcome model and the abovementioned evidence, we contend that hotel employees are beset with heightened JIS and therefore suffer from depletion of emotional resources.…”
Section: Emotional Exhaustion As a Mediatormentioning
confidence: 85%
“…job satisfaction, turnover intentions, etc.) in a mediating manner (Cheung and Tang, 2010;Jabutay et al, 2023;Um and Harrison, 1998). Drawing upon the SSO model, we posit that stressors, workload, and career shock lead to emotional exhaustion, which in turn hinders entrepreneurial career commitment.…”
Section: Career Shock and The Impact Of Stressmentioning
confidence: 99%